Low-temperature wetting of sapphire using Sn–Ti active solder alloys. Issue 17 (1st December 2019) - Mu, Dekui; Feng, Kuiyuan; Lin, Qiaoli; Huang, Han
Abstract: Monocrystalline alumina, known as sapphire, is one of the most commonly used ceramics in electronic devices. Understanding its wettability is thus of great importance for its engineering applications. In this work, the low-temperature wetting mechanisms of Sn–Ti active solder alloy on C-plane sapphire was comprehensively studied using the sessile drop method. The addition of 0.1 wt % Ti was found to effectively improve the wettability of Sn–Ti alloys, and the lowest contact angle on the sapphire substrate was achieved at 950 °C when Ti content was increased to 3 wt%. Thermal dynamics analysis and experimental results indicated that the isothermal spreading of Sn–3Ti alloy is controlled by the Ti adsorption in the vicinity of wetting triple line. Moreover, sapphire was successfully brazed using Sn–3Ti alloy at 500, 550, and 600 °C, and the maximum shear strength was measured as 30.3 MPa. Our understanding of the wettability of sapphire provides the fundamental theory for developing new bonding technique for this important crystal.